From Supervision to Opportunity: Reimagining Probation and Parole. Issue 1 (May 2022) - Harding, David J.; Western, Bruce; Sandelson, Jasmin A.
Across a variety of measures of safety and rehabilitation, our current systems of parole and probation are failing. Research shows that community supervision fails to reduce crime; traps its subjects in cycles of criminal justice involvement; is excessively punitive; and creates widespread harm to individuals, families, and communities—all while failing to significantly contribute to the social and economic integration of those under its control. We argue for a wholesale reform of community supervision, including the abandonment of current monitoring and control functions, and the repurposing of resources into systems of support for the hundreds of thousands of people leaving prison and jail every year. We also provide an overview to the articles assembled for this volume, which chart the challenges facing those on community supervision and offer a roadmap of potential policy solutions for improving the life chances of formerly incarcerated and justice-involved people.